Mechanism of erythropoietin-induced M2 microglia polarization via Akt / Mtor / P70S6k signaling pathway in the treatment of brain injury in premature mice and its effect on biofilm. Issue 5 (2nd May 2022) - Wu, Xiuling; Wang, Bo; Ma, Qiling; Zhang, Yunfang; Xu, Ji; Zhang, Zhongyuan; Chen, Guangfu
ABSTRACT: We investigated the mechanism of erythropoietin (EPO) in brain injury in premature mice based on Akt/mTOR/p70S6K signaling pathway. The brain injury model group of premature mice was obtained by intraperitoneal injection of lipopolysaccharide during pregnancy. Normal mice were taken as the control group. The model mice were divided into low-dose EPO (1, 000 IU/kg, L-EPO), medium-dose EPO (2, 500 IU/kg, M-EPO), and high-dose EPO groups (5, 000 IU/kg, H-EPO) by intraperitoneal injection. The levels of malondialdehyde (MDA) and total superoxide dismutase (T-SOD) were detected. TUNEL staining and Western blotting were used to detect the differences in neuronal apoptosis index (AI), microglial polarization marker protein, and Akt/mTOR/p70S6K-related protein expression levels in each group. Compared with the control group, the protein levels of AI, MDA, Bax, and iNOS in the model, L-EPO, and M-EPO groups were significantly increased, while the T-SOD level and Bcl-2, ARG1, p-Akt, p-mTOR, and p-70S6K protein levels were significantly decreased ( P < 0.05). Compared with the model group, AI, MAD levels and Bax, iNOS protein expression levels in L-EPO, M-EPO, and H-EPO groups were significantly decreased, while T-SOD level and Bcl-2, ARG1, p-Akt, p-mTOR, and p-70S6K protein levels were significantly increased. The changes were dose-dependent. In summary, EPO can activate microglia transformation from M1 to M2 through Akt/mTOR/p70S6K signaling pathway. Graphical abstract: uf0001